Combining Models and Commodity Chain Research for Making Long-Term Projections of Port Throughput: an Application to the HamburgLe Havre Range - Langen, Peter W. de; Meijeren, Jaco van; Tavasszy, Lóránt A. (European Journal of Transport and Infrastructure Research, 2012)
Long term projections of cargo throughput are indispensable for port development plans. Although commodity flow projections are useful for governments, port authorities, terminal operating companies and port users, scientific research on commodity flow projections for ports is limited. Existing studies generally use econometric models that assume stable relationships between growth of port throughput and such variables as GDP growth and trade growth. This paper presents a method that was developed as part of the Port Vision 2030 project of Port of Rotterdam Authority. The method combines a model with expert judgement and commodity specific research. This combination enables incorporating disruptions of past growth patterns. The contribution of this paper is the description of this method, its application to the volumes in 2030 of all major commodities handled in the Hamburg – Le Havre range, with four different scenarios, while most studies deal with a few commodities in one port, and often for a shorter period and with less scenarios. The results show that in all scenarios, total throughput is expected to rise, although in three scenarios not as fast as in the previous two decades. Furthermore, intermediates and container flows are expected to continue to grow, while throughput of raw materials (iron ore, crude oil) may decline.